Determining trends for perceived levels of corruption - Johann Graf Lambsdorff (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2005)
The Transparency International Corruption Perceptions Index is a composite index with a focus on cross-section information. The usage of the data in the form of time series has been discouraged in the past, due to changes in the composition of sources. Basing assessments only on sources that continuously enter the index, such time series are provided here, ranging from 1995 to 2005. Panel data regressions reveal how the sources' time series information is related to each other, suggesting a method for assembling panel data. Regressing a linear time trend on the standardized sources provides an assessment of the significance of a simple trend for each of 61 countries.
Keywords: 330